2007
DOI: 10.1176/appi.ps.58.9.1219
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making Preferences of People With Severe Mental Illness

Abstract: Most clients with severe mental illnesses prefer shared decision making, particularly in relation to their mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 5 publications
5
73
1
1
Order By: Relevance
“…In relation to involvement, patients were markedly more passive in treatment decisions than in social or financial decisions, again consistent with existing literature (26). A previous analysis of the CEDAR study data found that even more active involvement in decision-making than the patient stated as desired was associated 14 with higher satisfaction, indicating that a clinical orientation towards empowering may improve satisfaction for patients (27).…”
Section: Discussionsupporting
confidence: 85%
“…In relation to involvement, patients were markedly more passive in treatment decisions than in social or financial decisions, again consistent with existing literature (26). A previous analysis of the CEDAR study data found that even more active involvement in decision-making than the patient stated as desired was associated 14 with higher satisfaction, indicating that a clinical orientation towards empowering may improve satisfaction for patients (27).…”
Section: Discussionsupporting
confidence: 85%
“…Decision-making by mental health consumers, including the shared decision-making that plays a positive role in mental health treatment (Adams et al 2007;Deegan and Drake 2006), is a complex process deserving of further study. It will clearly entail the interaction of scientific evidence and recovery principles (Tanenbaum 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature is less developed than in many other specialties (Adams et al 2007), studies do show that adults with psychiatric illnesses (even severe illnesses) generally want information and active participation in decision making about their care (Simon et al 2009) and that the great majority are capable of understanding treatment choices and making rational decisions (Carpenter et al 2000;Grisso and Applebaum 1995;Stroup et al 2005). The mental health studies demonstrate that shared decision making interventions improve decision making (more knowledge, participation, and congruence with values), and some studies have shown improved adherence with treatment and satisfaction with care (Simon et al 2009).…”
Section: Introductionmentioning
confidence: 99%